Systematic Literature Review: Project Based Learning Learning Model To Improve Students' Learning Interest In Science Subjects In Elementary Schools - Azizah, Hikmatul; Firmansah, Deri; Yanti, Yuli (Kilau Publishing, 2025)
Low interest of elementary school students in science/science subjects, which results in a lack of active participation in learning and achievement of learning outcomes. The application of the project-based learning model, also known as Project-Based Learning (PjBL), is considered an alternative that can address this problem. Science learning becomes interesting and contextual for students. The purpose of this study is to see how the PjBL model helps increase students' interest in science/science subjects in elementary school. The Systematic Literature Review (SLR) approach was used in this study, and data collection techniques were used through Publish or Perish and Google Scholar. From a total of 200 articles found, a selection process was carried out based on inclusion and exclusion criteria, until 10 relevant articles were obtained for further analysis. The results of the study show that the consistent application of the PjBL model is able to increase students' learning interest through active involvement, contextual learning, and collaboration in completing projects. Factors that support the success of PjBL include the relevance of the project to student life, the appropriate use of learning media, community support, and systematic planning. The implications of this study suggest that primary school teachers need to consider the use of the PjBL model as the main learning strategy, especially in science/science subjects, to build a stronger and more sustainable interest in learning among students.